O-274 Cancer in Children Born after Frozen-Thawed Embryo Transfer: A Cohort Study. (30th June 2022) - Sargisian, N; Lannering, B; Petzold, M; Opdahl, S; Gissler, M; Pinborg, A; Henningsen, A.K; Tiitinen, A; Romundstad, L.B; Lærke Spangmose, A; Bergh, C; Wennerholm, U.B
Abstract: Study question: Do children conceived after assisted reproductive technology (ART), particularly after frozen/thawed embryo transfer (FET), have a higher risk of cancer? Summary answer: Children born after FET have a higher risk of childhood cancer than children born after fresh embryo transfer and spontaneous conception. What is known already: Previous studies on the association of ART conception and risk of childhood cancer show conflicting results. Worldwide, the number of children born after FET increases and in many countries the number of children born after FET now exceeds the number of children born after fresh embryo transfer. Children born after FET are at increased risk of macrosomia which has been associated with a higher risk of childhood cancer. Study design, size, duration: This large Nordic registry-based cohort study included 171 774 children born after use of ART and 7 772 474 children born after spontaneous conception during a study period of up to three decades (Denmark 1994-2014, Finland 1990-2014, Norway 1984-2015 and Sweden 1985-2015). Participants/materials, setting, methods: Cancer rates in children born after each conception method were determined by cross-linking data from national ART and birth registries, national cancer and population registries. The primary outcome was any cancer, and secondary outcomes were 12 cancer subgroups according to the International Classification of Childhood Cancer (ICCC-3). Children were followed from birth to cancer diagnosis, death, emigration, age 18 years or the end of the study period, whichever came first. Main results and the role of chance: Mean follow up was 9.9 years for children born after ART and 12.5 years for children born after spontaneous conception. Incidence rate (IR) of any cancer before 18 years of age was 19.3/100 000 person-years for children born after ART (329 cases) and 16.7/100 000 person-years for children born after spontaneous conception. Adjusted hazard ratio (aHR) was 1.08, 95% confidence interval (CI) 0.96-1.21. Adjustment was performed for sex, plurality, country of birth, year of birth, maternal age at birth, and parity. Children born after FET had a higher risk of any cancer (48 cases, IR 30.1/100 000 person-years), compared to both children born after fresh embryo transfer (227 cases, IR 18.8/100 000 person-years) (aHR 1.59, 95% CI, 1.15 to 2.20) and children born after spontaneous conception (aHR 1.64, 95% CI, 1.24 to 2.19). Adjustment for macrosomia (birthweight </≥4000 g), birthweight (continuous variable) or major birth defects only slightly attenuated the association. For cancer subgroups, higher risks of epithelial tumours and melanoma after any ART and of leukaemia after FET were observed. Limitations, reasons for caution: The main limitation is the number of children with cancer in the FET group. Although including a large cohort, the number of children with cancer is of moderate size. Furthermore, all data are observational, and residual confounding by factors as genetics, parental preconception health and lifestyle cannot be excluded. Wider implications of the findings: While risk of any cancer was not higher in children born after any ART, we found that children born after FET had a higher risk of cancer than children born after fresh transfer and spontaneously conceived children. These findings are important considering the increasing use of the freeze-all strategy. Trial registration number: ISRCTN11789826